Made-from-bone : trickster myths, music, and history from the Amazon - Hill, Jonathan David, 1954- (Interpretations of culture in the new millennium., 2009)
Recorded and transcribed by Jonathan Hill, this is a collection of mythic narratives from the indigenous Wakuénai of southernmost Venezuela. The central character throughout the tales is a trickster-creator, Made-from-Bone, who survives a prolonged series of life-threatening attacks.